2015
DOI: 10.1095/biolreprod.114.125740
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 Signaling Is a Major Mediator of the Female Tract Response to Seminal Fluid in Mice1

Abstract: Seminal fluid interacts with epithelial cells lining the female reproductive tract to induce expression of proinflammatory cytokines and chemokines, initiating immune tolerance mechanisms to facilitate pregnancy. TGFB cytokines are key signaling agents in seminal plasma but do not fully account for the female response to seminal fluid. We hypothesized that additional molecular pathways are utilized in seminal fluid signaling. Affymetrix microarray was employed to compare gene expression in the endometrium of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 77 publications
7
88
0
Order By: Relevance
“…The importance of toll-like receptor (TLR) 4 signaling has been implicated in SP-induced proinflammatory cytokine expression. In a similar fashion to TLR4 involvement during cumulus oocyte-complex (COC) expansion where endogenous TLR4 ligands induce the expression of proinflammatory mediators important for COC expansion, such as interleukin (IL) 6 (Shimada et al 2008), SP modulates TLR4-induced cytokines like colony-stimulating factor 2 (CSF2) (Shimada et al 2008, Schjenken et al 2015. The importance of SP exposure on embryonic development has also been demonstrated in mice and hamsters (Peitz & Olds-Clarke 1986, O et al 1988.…”
Section: Sp-induced Inflammation and Immune Modulation In Maternal Timentioning
confidence: 96%
“…The importance of toll-like receptor (TLR) 4 signaling has been implicated in SP-induced proinflammatory cytokine expression. In a similar fashion to TLR4 involvement during cumulus oocyte-complex (COC) expansion where endogenous TLR4 ligands induce the expression of proinflammatory mediators important for COC expansion, such as interleukin (IL) 6 (Shimada et al 2008), SP modulates TLR4-induced cytokines like colony-stimulating factor 2 (CSF2) (Shimada et al 2008, Schjenken et al 2015. The importance of SP exposure on embryonic development has also been demonstrated in mice and hamsters (Peitz & Olds-Clarke 1986, O et al 1988.…”
Section: Sp-induced Inflammation and Immune Modulation In Maternal Timentioning
confidence: 96%
“…The molecular basis of the female response to seminal fl uid mostly comes from laboratory studies using the mouse as a model (Robertson 2005 ;Robertson et al 1996 ;Schjenken et al 2015 ). At coitus in the mouse, seminal fl uid is deposited in the uterus and disseminates throughout the female reproductive tract, where it interacts with epithelial cells of the uterine lumen to activate gene expression and synthesis of several proinfl ammatory cytokines and chemokines.…”
Section: Seminal Fluid and The Peri-conception Infl Ammatory Responsementioning
confidence: 99%
“…More recently, several other cytokines and chemokines including interleukin-6 (IL6), tumor necrosis factor (TNF), C-X-C motif chemokine ligand-1 (CXCL1, also known as growth regulated alpha protein, GRO or KC), CXCL2 (macrophage infl ammatory protein-2, MIP2), C-C motif chemokine ligand-3 (CCL3, macrophage infl ammatory protein-1 alpha, MIP1A), and granulocyte colony-stimulating factor (GCSF) have been identifi ed as elevated in the mouse uterus during the immediate post-coital phase (Schjenken et al 2015 ;Sanford et al 1992 ;Robertson et al 1998 ;Pollard et al 1998 ;Johansson et al 2004 ). Seminal plasma is required for much of this response as coitus with males rendered seminal fl uid defi cient, by surgery to remove seminal vesicles and vasectomy, results in either no induction or substantially reduced cytokine induction (Schjenken et al 2015 ). In contrast, delivery of seminal plasma by vasectomised males induces a response comparable to that induced by intact males (Robertson et al 1996 ).…”
Section: Seminal Fluid and The Peri-conception Infl Ammatory Responsementioning
confidence: 99%
“…At the same time, we think that more detailed analysis is needed in order to explore the mechanisms. Schjenken et al and Sharkey et al suggested the levels of G-CSF increased during the interaction of seminal fluid and epithelial cells, further contributing to the conception [4,5]. Meanwhile, as for the patients undergoing assisted reproduction treatment, the better clinical pregnancy outcomes could be observed by adding the G-CSF to embryo culture medium in some extent [6].…”
mentioning
confidence: 99%